An In-Depth Investigation of the Complex Interplay between Entrepreneurial Leadership and Employee’s Individual Outcomes: Uncovering the Multifaceted Dynamics of Organizational Success - Muhammad Atif Bashir; Shakeel Sarwar; Syed Muhammad Javed Iqbal; Rashid Khurshid (International Journal of Business and Economic Affairs, 2023)
The relationship between employee productivity and organisational success has become an increasingly prominent area of research. Numerous studies have demonstrated that individual employee outcomes are closely linked to business units and overall organisational performance. Creativity and innovation play a crucial role in an organisation’s ability to gain and maintain a strategic advantage over competitors, particularly for Small and Medium-sized Enterprises (SMEs), which are crucial to a country’s economic and social development. While leadership is essential for employee motivation and organisational development, the precise nature of the relationship between leadership style and individual employee outcomes remains unclear. This study aims to establish a comprehensive framework for understanding the impact of leadership on employee performance, exploring novel motivations for achieving individual employee outcomes that ultimately enhance employee and organisational performance. Data were collected through interviews with 26 consenting employees, employing open-ended questions and note-taking, and were analysed using a thematic approach. Data analysis revealed five fundamental key themes that emerged from the collected data from various workers of SMEs concerning individual outcomes in the organisation. The outcomes of this study provide valuable insights for managers and leaders in SMEs as they strive to enhance employee performance and organisational effectiveness. The findings offer a fresh perspective on the relationship between leadership style and employee outcomes, highlighting the importance of novel approaches that encourage individual employee growth and development. The study’s significance extends beyond the SME context, as its findings provide valuable insights for businesses seeking to improve their organisational performance.